Pitcairnia frequens (Bromeliaceae), a neglected new species from Morro dos Seis Lagos, Amazonas, Brazil - P., Saraiva D.; C., Forzza R. (Phytotaxa, 2012)
This paper formally describes a nomem in schedulum for a Pitcairnia endemic to Morro dos Seis Lagos, São Gabriel da Cachoeira, Amazonas in North Brazil. It was first collected by Cyl Farney in 1987 in “Projeto Flora Amazônica”. The duplicate sent to New York Botanical Garden Herbarium was later annotated as Pitcairnia frequens by L. B. Smith and B. Holst, however it was never described and published.